PENGENALAN DAN PENGAPLIKASIAN VBA MACRO DALAM MENINGKATKAN EFISIENSI PENGOLAHAN DATA MENGGUNAKAN MS OFFICE EXCEL DI SMAN 1 CIRUAS - Muflihah Muflihah; Sarah Caesarani (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
In an education department, there will be a compulsory course, for example the Field Experience Peraktik (PPL) course. Field Experience Practice is one of the compulsory courses for all Education students, especially Information Technology Education (PTI) at Bina Bangsa University. Peraktik Field Experience itself aims to train students in applying scientific methods that have been obtained at Bina Bangsa University majoring in Information Technology Education. Field Peraktik as a lecturer was held at SMAN 1 Ciruas for the 2023/2024 academic year of Bina Bangsa University in the form of service. Field Experience Practice at SMAN 1 Ciruas aims to increase student motivation through Information technology subjects.  In a high school learning system in Information & communication Technology (ICT) subjects, there are various kinds of material, one of which applies the Ms. Excel application basically. Microsoft Excel is an application included in Microsoft office that is required to be studied in every school in ICT subjects today. Visual Basic for Applications (VBA) Macro is a type of programming application contained in Microsoft office, one of which uses ms. Excel. The use of VBA Macros in Ms. Excel itself increases knowledge of how to process data automatically